2013
DOI: 10.4028/www.scientific.net/amr.726-731.2567
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Start-Up and Performance of the EGSB Reactor Treating Actual Coking Wastewater when Seeded with Digestion Sludge

Abstract: To accomplish rapidly the granulation process of digestion sludge for the treatment of actual coking wastewater and meanwhile achieve high COD, phenol, SCN- and CN- removal, the EGSB reactor was employed with two operation stages. StageI: Granular sludge was formed from digestion sludge using brewery wastewater as substrate in the anaerobic way (meanwhile adding little granules, which were 1/7 of the total biomass). StageII: Granular sludge was acclimatized with the actual coking wastewater through continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The DEGBR designed for this study performed well in comparison to the EGSB used in another study, whereby it was indicated that the performance was attributed to a rapid start-up of the EGSB, in which brewery wastewater sludge was used in the treatment of slaughterhouse wastewater. It was determined that the sludge could develop faster within a period of 10 days in the EGSB reactor, with few detached sludge granules, achieving removal efficiencies of up to 72.9% of COD at an operational hydraulic retention time (HRT) of 12.1 h [22].…”
Section: The Performance Of the Debgrmentioning
confidence: 99%
“…The DEGBR designed for this study performed well in comparison to the EGSB used in another study, whereby it was indicated that the performance was attributed to a rapid start-up of the EGSB, in which brewery wastewater sludge was used in the treatment of slaughterhouse wastewater. It was determined that the sludge could develop faster within a period of 10 days in the EGSB reactor, with few detached sludge granules, achieving removal efficiencies of up to 72.9% of COD at an operational hydraulic retention time (HRT) of 12.1 h [22].…”
Section: The Performance Of the Debgrmentioning
confidence: 99%